2019
DOI: 10.33314/jnhrc.v0i0.1213
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Syndrome in Students of a Teaching Hospital

Abstract: Background: Premenstrual syndrome is group of psychosomatic symptoms which occurs during second half of menstrual cycle. Significant number of reproductive aged females suffer from it with its impact on their daily activities. This study was conducted to assess the prevalence, severity and impacts of Premenstrual syndrome on female students of a teaching hospital of Kathmandu, Nepal.Methods: This cross-sectional study was conducted among female students of a teaching hospital from Kathmandu over a period of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
36
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 0 publications
6
36
1
3
Order By: Relevance
“…In the PMDD category, a study in India and Nepal mostly reported anxiety/tension (100%), tearfulness (100%), and decreased interest in work (100%). 3,15 Another study showed mostly physical symptoms (91.4%), irritability (84.5%), and anxiety/tension (79.3%). 5 In a study in Iran, the most reported symptom in PMDD and moderate to severe PMS category was anger/irritability (99.2%; 88.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the PMDD category, a study in India and Nepal mostly reported anxiety/tension (100%), tearfulness (100%), and decreased interest in work (100%). 3,15 Another study showed mostly physical symptoms (91.4%), irritability (84.5%), and anxiety/tension (79.3%). 5 In a study in Iran, the most reported symptom in PMDD and moderate to severe PMS category was anger/irritability (99.2%; 88.7%).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] The incidence of PMS worldwide also varies from mild (70%-95%), moderate (20%-70%), and severe PMS/PMDD (1%-20%). 3,5,[12][13][14][15][16] A difficulty with PMS diagnosis is identifying whether patients need treatment. Different scales and methods for PMS diagnosis are used worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Os autores relataram que a prevalência dos sintomas pré-menstruais foi superior a 90% nas últimas quatro semanas, sendo que destes, 60,8% tinham sintomas leves, cerca de 34,4% apresentou sintomatologia moderada e apenas 4,8% sintomas graves consideradas com TDPM. Shrestha et al (2019) realizaram um estudo prospectivo, entre 285 estudantes de um hospital universitário no Nepal e observaram que 72,3% relataram pelo menos um sintoma de SPM de intensidade moderada a grave, todas as estudantes estavam no ensino superior, em cursos da saúde, 92,6% eram de áreas urbanas e 80,7% tinham ciclos menstruais regulares, semelhante às características da amostra deste estudo.…”
Section: Discussionunclassified
“…Shrestha et al (2019) foram sintomas relatados por pelo menos 44,2% das 285 voluntárias pesquisadas. No âmbito do TDPM, Śliwerski e Bielawska-Batorowicz (2019) afirmaram que, cerca de 30 a 80% das mulheres que sofrem com essa forma mais grave da SPM, já tiveram pelo menos um episódio depressivo no passado.…”
unclassified
“…A systematic review reported 30%-99.5% prevalence of PMS in Iran, 3 while a recent study in Nepal reported that 72% of university students had at least one symptom of PMS. 4 The common clinical and psychological symptoms of PMS include depression, mood fluctuations, nervousness, irritability, fatigue, overeating, weight gain, breast tenderness, muscle and joint pain, abdominal bloating, diarrhoea and performance reduction. [5][6][7] Most study findings show that 5%-8% of women have mild to severe symptoms while some studies estimate 20% of all fertile women experience clinically significant premenstrual complaints.…”
Section: Introductionmentioning
confidence: 99%